2013
DOI: 10.1186/1475-2875-12-233
|View full text |Cite
|
Sign up to set email alerts
|

Inland valley rice production systems and malaria infection and disease in the forest region of western Côte d’Ivoire

Abstract: BackgroundThis study aimed to determine the epidemiological impact of rice cultivation in inland valleys on malaria in the forest region of western Côte d’Ivoire. The importance of malaria was compared in terms of prevalence and parasite density of infections and also in terms of clinical malaria incidence between three agro-ecosystems: (i) uncultivated inland valleys, (R0), (ii) inland valleys with one annual rice cultivation in the rainy season, (R1) and (iii) developed inland valleys with two annual rice cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
3
16
5
Order By: Relevance
“…Different age groups among school-aged children have been used to estimate the risk of malaria infection in an area. From examples in Uganda [ 39 ], Malawi [ 40 ], Mozambique [ 41 ], Equatorial Guinea [ 40 ], Côte d’Ivoire [ 42 ], Senegal [ 43 ], Tanzania [ 44 ], school-age children used for surveys were between 5 and 9 years of age. Other studies conducted in children in Uganda, Kenya, Tanzania, Mali, Nigeria, Central African Republic, Cameroon, Congo Brazzaville, Ethiopia, Somalia, Yemen and Ghana have selected ages from 0.5 up to 18 years [ 19 , 20 , 45 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different age groups among school-aged children have been used to estimate the risk of malaria infection in an area. From examples in Uganda [ 39 ], Malawi [ 40 ], Mozambique [ 41 ], Equatorial Guinea [ 40 ], Côte d’Ivoire [ 42 ], Senegal [ 43 ], Tanzania [ 44 ], school-age children used for surveys were between 5 and 9 years of age. Other studies conducted in children in Uganda, Kenya, Tanzania, Mali, Nigeria, Central African Republic, Cameroon, Congo Brazzaville, Ethiopia, Somalia, Yemen and Ghana have selected ages from 0.5 up to 18 years [ 19 , 20 , 45 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would have been interesting to employ additional diagnostic assays, particularly polymerase chain reaction (PCR) methods that are highly sensitive [ 52 , 53 ] and thus would allow to clarify the false-negative diagnoses obtained with RDT compared to microscopy. Third, the survey was carried out during the dry season when malaria transmission is low [ 4 , 54 , 55 ], which might have resulted in an underestimation of the overall P. falciparum prevalence. It is conceivable that the overall P. falciparum prevalence among school-aged children is somewhat higher during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this finding are offered for consideration. First, in Côte d'Ivoire 100% of the population is at risk of Plasmodium infection [3] and previous research concluded that malaria transmission is perennial [45] , [46] . Constant exposure from early childhood onwards leads to naturally acquired immunity to malaria at an early age [47] .…”
Section: Discussionmentioning
confidence: 99%